A kind of thermoplastic polyurethane hot melt adhesive and its preparation method and application
Through the reaction of polyols and functional particles with specific ratios, the dense three-dimensional network structure and composite particle structure of polyurethane hot melt adhesive are constructed, which solves the problem of insufficient stability, waterproofness and antistatic properties of polyurethane hot melt adhesive in high temperature environments. Achieve more efficient curing and better comprehensive performance.
Patent Information
- Application Number
- CN202411280880.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The existing polyurethane hot melt adhesives are insufficient in high temperature environments, waterproof, antistatic and aging resistance, and cannot meet the demand for improving adhesive performance in electronic products and automobile industries.
Using specific ratios of raw materials such as polyol compositions, polyisocyanates, functional polymers, plasticizers, functional particles and catalysts, the dense three-dimensional network structure and composite particle structure are constructed through the reaction connection between functional polymers and functional particles, and the structure of dense three-dimensional network structure and composite particle structure are improved. The mechanical and mechanical properties of hot melt adhesives, waterproofness, anti-static properties and aging resistance.
It significantly improves the curing rate, deep curing effect, waterproofness, antistatic properties and thermal stability of polyurethane hot melt adhesive, meets the high requirements for adhesive performance in electronic products and automobile industries, and provides a more comprehensive performance quality. .
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of hot melt adhesives, and in particular to a thermoplastic polyurethane hot melt adhesive and a preparation method and application thereof. Background Art
[0002] Thermoplastic polyurethane (TPU) hot melt adhesive is a high-performance adhesive that combines the excellent properties of TPU with the ease of use of hot melt adhesive. This type of adhesive is solid at room temperature and becomes liquid when heated, allowing it to bond a variety of materials. Once cooled, it re-hardens to form a strong bond.
[0003] Polyurethane hot-melt adhesives are widely used in various industries, including automotive, electronics, and packaging, due to their excellent bonding properties, flexibility, and weather resistance. A typical polyurethane hot-melt adhesive formulation typically contains polyols, polyisocyanates, and other additives. These components react at a specific temperature to form a hot-melt adhesive with excellent properties.
[0004] In recent years, with the increasing demands for lightweighting and environmental protection in the electronics and automotive industries, higher requirements have been placed on the performance of adhesives used inside these products. These requirements typically include stability under high-temperature conditions, stronger adhesive strength, better waterproofing, superior aging resistance, and good antistatic properties. However, existing polyurethane hot melt adhesives focus more on improving the mechanical and electrical properties after curing, while other more diverse properties rely more on the properties of polyurethane itself or some common fillers, which cannot meet the performance requirements of current products for hot melt adhesives.
[0005] Therefore, in order to solve the above problems, this application provides a thermoplastic polyurethane hot melt adhesive and its preparation method. The thermoplastic polyurethane hot melt adhesive prepared by this application not only has good mechanical properties and a more efficient curing rate and deep curing effect, but also significantly improves the waterproofness, tack, aging resistance, antistatic properties and thermal stability of polyurethane hot melt adhesive, providing more comprehensive performance quality, thereby meeting the performance requirements of existing electronic products and the automotive industry for adhesives, and has excellent application prospects. Summary of the Invention
[0006] In order to solve the above problems, the first aspect of the present application provides a thermoplastic polyurethane hot melt adhesive, the raw materials of which are, in parts by mass: 50 to 80 parts of a polyol composition, 15 to 25 parts of a polyisocyanate, 8 to 12 parts of a functional polymer, 5 to 8 parts of a plasticizer, 1 to 2 parts of a chain extender, 0.3 to 1.2 parts of a catalyst, 1 to 3 parts of an antioxidant, and 10 to 15 parts of functional particles.
[0007] As a preferred embodiment, the mass ratio of the polyol composition, the polyisocyanate, and the functional polymer is (6~7.5):(1.6~2.2):(1~1.2).
[0008] As a preferred embodiment, the mass ratio of the polyol composition, the polyisocyanate, and the functional polymer is (6.5~7.2):(1.8~2):(1~1.1).
[0009] As a preferred solution, the mass ratio of the polyol composition, the plasticizer and the functional particles is (6-7.5): (0.5-0.8): (1.1-1.4).
[0010] As a preferred solution, the mass ratio of the polyol composition, the plasticizer and the functional particles is (6.5-7.2): (0.6-0.7): (1.2-1.3).
[0011] As a preferred solution, the polyol composition is a composition of polyether polyol, polyester polyol and polyurea polyol.
[0012] As a preferred embodiment, the mass ratio of the polyether polyol, polyester polyol and polyurea polyol is (2.5~3.5):(3.5~4.2):(0.8~1.2).
[0013] As a preferred solution, the mass ratio of the polyether polyol, polyester polyol and polyurea polyol is (2.8-3): (3.5-3.8): (1-1.2).
[0014] As a preferred solution, the functionality of the polyether polyol is 3.
[0015] As a preferred solution, the polyether polyol is a copolyether triol of propylene oxide and ethylene oxide.
[0016] As a preferred embodiment, the number average molecular weight of the polyether polyol is 3000~4000 Da.
[0017] As a preferred embodiment, the hydroxyl value of the polyether polyol is 25~30 mgKOH / g.
[0018] As a preferred embodiment, the hydroxyl value of the polyether polyol is 26~28 mgKOH / g.
[0019] As a preferred solution, the polyester polyol is polyadipate polyester diol.
[0020] As a preferred embodiment, the number average molecular weight of the polyester polyol is 2000~3000 Da.
[0021] As a preferred embodiment, the polyurea content of the polyurea polyol is 15-23%.
[0022] As a preferred embodiment, the polyurea polyol has a number-average molecular weight of 5000~6500 Da.
[0023] As a preferred embodiment, the hydroxyl value of the polyurea polyol is 25~33 mgKOH / g.
[0024] As a preferred embodiment, the hydroxyl value of the polyurea polyol is 28~30 mgKOH / g.
[0025] As a preferred embodiment, the polyisocyanate is hexamethylene diisocyanate.
[0026] As a preferred embodiment, the preparation method of the functional polymer includes the following steps: S1: Mixing trimer 1,2-propylene glycol and polycarbonate diol evenly in a high-speed mixer, and then vacuum dehydrating at 120~130℃ for 2~3h to obtain a premix; S2: Adding the premix to a reaction vessel, heating to 70~85℃, and then adding hexamethylene diisocyanate, toluene diisocyanate, and dibutyltin dilaurate, and maintaining the temperature for 2~4h; S3: After the reaction is completed, naturally cooling to 60~65℃ and discharging the product, and then washing the product with ethanol circulation 2~3 times to obtain the final product.
[0027] As a preferred embodiment, the mass ratio of the trimer 1,2-propylene glycol, polycarbonate diol, hexamethylene diisocyanate and toluene diisocyanate is (10~20):(5~10):(15~20):(5~10).
[0028] As a preferred embodiment, the mass ratio of the trimer 1,2-propylene glycol, polycarbonate diol, hexamethylene diisocyanate and toluene diisocyanate is (12~15):(6~8):(16~19):(8~10).
[0029] As a preferred embodiment, the mass ratio of the trimer 1,2-propylene glycol to dibutyltin dilaurate is (10~20):(0.01~0.1).
[0030] The functional polymers incorporated in this application effectively improve the mechanical, waterproof, aging-resistant, and antistatic properties of polyurethane hot melt adhesives. The addition of these functional polymers not only participates in the construction of the main chain unit during the formation of the polyurethane hot melt adhesive, but also introduces more active groups and sites onto the polyurethane chains. The presence of these sites significantly enhances the construction of a dense three-dimensional network structure within the internal system during hot melt adhesive bonding. This not only effectively improves the curing rate and deep curing quality in practical applications, but also enhances external stress resistance through strong internal intermolecular forces under external forces, thereby achieving excellent mechanical properties and dense waterproof performance after curing.
[0031] On the other hand, the added functional polymers can form a good reactive bond with the functional particles through their numerous active sites, thereby significantly improving the adhesion of the functional polymers to the functional particles. This not only greatly reduces the aggregation of functional particles within the hot melt adhesive system, but also serves as an excellent flow carrier for the functional particles in the hot melt adhesive system, thus significantly improving the effect of the functional particles in the hot melt adhesive system. This enhances the waterproof, high temperature resistance, aging resistance, and antistatic properties. Furthermore, it significantly improves the fixation of functional particles in the cured system, thereby avoiding the impact of migration and segregation of functional particles on the adhesion of the hot melt adhesive, and ultimately achieving excellent comprehensive performance.
[0032] As a preferred solution, the plasticizer is a combination of trioctyl citrate and epoxidized soybean oil.
[0033] As a preferred embodiment, the mass ratio of trioctyl citrate to epoxidized soybean oil is (2~4):(4~5.5).
[0034] As a preferred embodiment, the chain extender is a combination of 1,2-propanediamine and diethyltoluenediamine.
[0035] As a preferred solution, the mass ratio of 1,2-propylenediamine to diethyltoluenediamine is (3-4): (1-1.5).
[0036] As a preferred solution, the catalyst is dibutyltin dilaurate or dibutyltin dioctoate.
[0037] As a preferred solution, the catalyst is dibutyltin dioctoate.
[0038] As a preferred solution, the antioxidant is antioxidant 1076.
[0039] As a preferred solution, the preparation method of the functional particles includes the following steps: S1: mixing carbon black and titanium dioxide and adding them to deionized water, adding succinic anhydride and triisostearyl titanate isopropyl, heating the mixture to 60-70°C and keeping the mixture for reaction for 2-3 hours, and centrifuging and washing to obtain premixed particles; S2: adding the premixed particles and zinc nitrate to DMF solvent, heating the mixture to 45-55°C and keeping the mixture for reaction for 3-4 hours, then adding a DMF solution of 2,5-dihydroxyterephthalic acid, sealing the reactor, heating the mixture to 125-130°C, stirring the mixture at 120-150 rpm for reaction for 22-26 hours, cooling the mixture naturally to room temperature after the reaction is completed, centrifuging, and washing with methanol to obtain preproduct particles; S3: adding the preproduct particles to deionized water with ammonia to adjust the pH to 9.5-10, adding tetraethyl orthosilicate and ethanolamine, heating the mixture to 60-65°C and keeping the mixture for reaction for 2-3 hours, centrifuging and filtering the mixture after completion, washing the mixture with ethanol for 2-3 times, and drying the mixture to obtain the preproduct particles.
[0040] As a preferred embodiment, the mass ratio of carbon black, titanium dioxide, succinic anhydride and triisostearoyl titanate is (2.5~3):(0.5~0.8):(1.2~1.5):(0.2~0.4).
[0041] As a preferred embodiment, the mass ratio of the premixed particles, zinc nitrate, and 2,5-dihydroxyterephthalic acid is (4~5):(2.2~2.5):(1.4~1.8).
[0042] As a preferred embodiment, the mass ratio of the preproduct particles, tetraethyl orthosilicate and ethanolamine is (4.5~5):(0.5~0.8):(0.1~0.15).
[0043] As a preferred embodiment, the titanium dioxide has an average particle size of 5-10 nm.
[0044] As a preferred embodiment, the average particle size of the carbon black is 20~30 nm.
[0045] The functional particles added in this application can significantly improve the antistatic, mechanical, curing waterproof, and aging resistance properties of polyurethane hot melt adhesives. Firstly, the added functional particles, through the composite structure formed by carbon black and titanium dioxide, enhance the attraction of free electrons. Furthermore, the composite structure significantly increases the length of the electron flow path and strengthens the electron flow velocity through the aggregation of electrons and electron holes. This enables rapid electron transport and the formation of a good static dissipation effect on the surface, resulting in excellent antistatic properties. Secondly, the addition of functional particles can create a more effective internal gradient structure after the hot melt adhesive has cured, through the framework particle structure located at the center of the particle composite structure. The presence of this structure can significantly increase the resistance and free path length of water molecules in the cured hot melt adhesive system, which not only greatly reduces the penetration rate of water molecules, but also effectively prevents them from agglomerating and forming moisture sites. On the surface of the cured hot melt adhesive, a rough surface structure can be formed by constructing an uneven surface structure, which can prevent the continuous aggregation between surface water molecules and greatly increase the difficulty of forming a continuous hydration layer on the surface, thereby obtaining excellent curing and waterproof performance. Finally, the added functional particle structure can also form a good steric hindrance between active molecules in the hot melt adhesive system, which not only increases the contact probability between active molecules and groups, but also increases the difficulty of their reaction, effectively reducing internal reactivity, thereby obtaining excellent high-temperature stability and aging resistance.
[0046] The second aspect of this application provides a method for preparing the above-mentioned thermoplastic polyurethane hot melt adhesive, specifically including the following steps: S1: Polyol composition, functional polymer, plasticizer and chain extender are preferentially added to the reaction vessel, the temperature is raised to 55~60℃, and the mixture is stirred at 60~80 rpm for 2~4 hours until the moisture content of the mixture is ≤0.03wt%; S2: The remaining raw materials are added to the reaction vessel, the stirring speed is increased to 100~140 rpm and the temperature is raised to 90~110℃, and the reaction is maintained at this temperature for 2~4 hours; S3: After the reaction is completed, the product is taken out, vacuum degassed for 1~1.5 hours and transferred to a storage container for dry inert gas protection, thus obtaining the product.
[0047] The third aspect of this application provides an application of the above-mentioned thermoplastic polyurethane hot melt adhesive in the automotive industry, electronics, packaging, and construction fields.
[0048] This application has the following beneficial effects:
[0049] 1. The thermoplastic polyurethane hot melt adhesive provided in this application not only has good mechanical properties and a more efficient curing rate and deep curing effect, but also can greatly improve the waterproofness, adhesion, aging resistance, antistatic and thermal stability of the polyurethane hot melt adhesive, providing more comprehensive performance quality, thereby meeting the performance requirements of existing electronic products and the automotive industry for adhesives, and has very excellent application prospects.
[0050] 2. A thermoplastic polyurethane hot melt adhesive provided in the present application, the added functional polymer can not only participate in the construction of the main chain segment unit during the formation process of the polyurethane hot melt adhesive, but also introduce more active groups and sites on the polyurethane chain segment. The presence of these sites can greatly improve the construction of a dense three-dimensional network structure of the internal system during hot melt adhesive bonding, not only effectively improving the curing rate and deep curing quality in actual use, but also improving the good external stress resistance effect through strong internal intermolecular forces when external forces act, thereby obtaining good mechanical and dense waterproof properties after curing.
[0051] 3. A thermoplastic polyurethane hot melt adhesive provided in the present application, the added functional polymer can form a good reaction connection with the functional particles through its more active sites, thereby greatly improving the adhesion of the functional polymer to the functional particles, not only greatly reducing the aggregation of functional particles inside the hot melt adhesive system, but also becoming an excellent fluidity carrier of functional particles in the hot melt adhesive system, thereby greatly improving the effect of functional particles in the hot melt adhesive system, improving waterproof, high temperature resistance, aging resistance and antistatic properties, and can greatly improve the fixation of functional particles in the cured system, thereby avoiding the influence of migration and segregation of functional particles on the adhesion of the hot melt adhesive, thereby obtaining excellent comprehensive performance.
[0052] 4. A thermoplastic polyurethane hot melt adhesive provided in the present application has functional particles added thereto that can enhance the attraction effect on free electrons through the composite structure formed by carbon black and titanium dioxide, and greatly increase the length of the electron flow path within the composite structure, and enhance the electron flow speed through the aggregation effect of electrons and electron holes, thereby being able to quickly transmit electrons and form a good static dissipation effect on the surface, thereby obtaining good antistatic properties.
[0053] 5. The thermoplastic polyurethane hot melt adhesive provided in this application incorporates functional particles that, after the hot melt adhesive has cured, form an internal gradient structure with a stronger barrier effect through the framework particle structure located at the center of the particle composite structure. The presence of this structure can significantly increase the resistance and free path length of water molecules in the cured hot melt adhesive system, which not only significantly reduces the penetration rate of water molecules, but also effectively prevents them from agglomerating and forming moisture sites. On the surface of the cured hot melt adhesive, a rough cured surface structure can be formed by constructing an uneven surface structure, which blocks the continuous aggregation between surface water molecules, greatly increases the difficulty of forming a continuous hydration layer on the surface, and thus obtains excellent cured waterproof performance. Detailed Implementation
[0054] The following will further illustrate and demonstrate the technical solutions described above in this application through specific implementation schemes. Furthermore, the following embodiments are merely practical examples used to illustrate and explain the content of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in this application should be covered within the scope of protection of this application.
[0055] In the following examples, unless otherwise specified, the raw materials are all commercially available products or can be prepared by methods well known to those skilled in the art.
[0056] Example 1
[0057] Example 1 provides a thermoplastic polyurethane hot melt adhesive, which, by weight, comprises: 71.5 parts of a polyol composition, 20 parts of a polyisocyanate, 10.5 parts of a functional polymer, 6.5 parts of a plasticizer, 1.8 parts of a chain extender, 0.6 parts of a catalyst, 1.5 parts of an antioxidant, and 12.6 parts of functional particles.
[0058] The polyol composition is a composition of polyether polyol, polyester polyol and polyurea polyol, and the mass ratio of the three is 3:3.6:1.1.
[0059] The polyether polyol is a co-ether triol of propylene oxide and ethylene oxide, with a number-average molecular weight of 4000 Da and a hydroxyl value of 26.5 mg KOH / g. It was purchased from Shandong Polychemical Co., Ltd. as product model 10LD28ZJ.
[0060] The polyester polyol is polyadipate polyester diol with a number average molecular weight of 3000 Da, which was purchased from Shandong Suihua Biotechnology Co., Ltd. and is a product of the corresponding molecular weight of the HY series.
[0061] The polyurea polyol has a polyurea content of 21.2%, a number average molecular weight of 6000 Da, and a hydroxyl value of 28.5 mgKOH / g. The polyurea polyol was purchased from Covestro as a Multranol 9151 product.
[0062] The polyisocyanate is hexamethylene diisocyanate.
[0063] The preparation method of the functional polymer includes the following steps, in parts by weight: S1: 14.5 parts of trimer 1,2-propylene glycol and 7.5 parts of polycarbonate diol are mixed evenly in a high-speed mixer and then dehydrated under vacuum at 125°C for 3 hours to obtain a premix; S2: The premix is added to a reaction vessel, heated to 80°C, and then 16.8 parts of hexamethylene diisocyanate, 8.8 parts of toluene diisocyanate, and 0.05 parts of dibutyltin dilaurate are added. The reaction is maintained at this temperature for 4 hours; S3: After the reaction is completed, the mixture is naturally cooled to 60°C and discharged. The product is washed three times with ethanol to obtain the final product.
[0064] Polycarbonate diol was purchased from Hubei Yamade Biopharmaceutical Co., Ltd. under the model PCDL-2000.
[0065] The industrial grade trimer 1,2-propylene glycol was purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.
[0066] The plasticizer is a composition of trioctyl citrate and epoxidized soybean oil, and the mass ratio of the two is 2.6:4.2.
[0067] Epoxidized soybean oil was purchased from Shandong Hongyunchang Chemical Technology Co., Ltd., which is a high-quality plasticizing grade epoxidized soybean oil product.
[0068] The chain extender is a composition of 1,2-propylene diamine and diethyltoluenediamine, and the mass ratio of the two is 3.4:1.3.
[0069] The catalyst is dibutyltin dioctoate.
[0070] The antioxidant is antioxidant 1076.
[0071] The preparation method of functional particles includes the following steps, by mass: S1: 2.8 parts carbon black and 0.68 parts titanium dioxide are mixed and added to 80 parts deionized water, 1.42 parts succinic anhydride and 0.26 parts isopropyl triisostearoyl titanate are added, and the mixture is heated to 65°C and kept at that temperature for 3 hours. After centrifugation and washing, premixed particles are obtained; S2: 4.4 parts premixed particles and 2.4 parts zinc nitrate are added to 80 parts DMF solvent, and the mixture is heated to 50°C and kept at that temperature for 3 hours. Then, 1.75 parts of 2,5-dihydroxyterephthalic acid DMF solution (20 parts in total) are added, the reaction vessel is sealed, and the temperature is raised to 128°C and 125°C. The reaction was stirred at rpm for 23.5 h. After the reaction was completed, the mixture was naturally cooled to room temperature, centrifuged and filtered, and washed with methanol to obtain the preproduct particles. S3: 4.8 parts of the preproduct particles were added to 100 parts of deionized water and ammonia water to adjust the pH to 9.8. 0.62 parts of tetraethyl orthosilicate and 0.14 parts of ethanolamine were added. The mixture was heated to 64℃ and kept at that temperature for 2.5 h. After the reaction was completed, the mixture was centrifuged and filtered, washed three times with ethanol, and dried to obtain the final product.
[0072] The average particle size of titanium dioxide is 5 nm; the average particle size of carbon black is 26 nm, and the corresponding particle size products were purchased from Mitsubishi Chemical in Japan.
[0073] The second aspect of this embodiment provides a method for preparing the above-mentioned thermoplastic polyurethane hot melt adhesive, specifically including the following steps: S1: Polyol composition, functional polymer, plasticizer and chain extender are preferentially added to the reaction vessel, the temperature is raised to 60°C, and the mixture is stirred at 80 rpm for 3 hours until the moisture content of the mixture is ≤0.03wt%; S2: The remaining raw materials are added to the reaction vessel, the stirring speed is increased to 120 rpm and the temperature is raised to 105°C, and the reaction is maintained at this temperature for 3 hours; S3: After the reaction is completed, the product is taken out, vacuum degassing is performed for 1 hour and the product is transferred to a storage container under dry inert gas protection to obtain the final product.
[0074] Example 2
[0075] Example 2 provides a thermoplastic polyurethane hot melt adhesive, which, by weight, comprises: 68.5 parts of a polyol composition, 17.5 parts of a polyisocyanate, 12 parts of a functional polymer, 5.2 parts of a plasticizer, 1.8 parts of a chain extender, 0.6 parts of a catalyst, 1.5 parts of an antioxidant, and 11 parts of functional particles.
[0076] The polyol composition is a composition of polyether polyol, polyester polyol and polyurea polyol, and the mass ratio of the three is 2.5:4.2:0.8.
[0077] The polyether polyol is a copolyether triol of propylene oxide and ethylene oxide, with a number average molecular weight of 4000 Da and a hydroxyl value of 26.5 mgKOH / g. It was purchased from Shandong Poly Chemical Co., Ltd. under the model number 10LD28ZJ.
[0078] The polyester polyol is poly(adipic acid polyester diol) with a number average molecular weight of 3000 Da, purchased from Shandong Suihua Biotechnology Co., Ltd. as a product of the corresponding molecular weight in the HY series.
[0079] The polyurea polyol has a polyurea content of 21.2%, a number average molecular weight of 6000 Da, and a hydroxyl value of 28.5 mg KOH / g. It was purchased from Covestro as Multranol 9151.
[0080] The polyisocyanate is hexamethylene diisocyanate.
[0081] The preparation method of the functional polymer includes the following steps, in parts by weight: S1: 14.5 parts of trimer 1,2-propylene glycol and 7.5 parts of polycarbonate diol are mixed evenly in a high-speed mixer and then dehydrated under vacuum at 125°C for 3 hours to obtain a premix; S2: The premix is added to a reaction vessel, heated to 80°C, and then 16.8 parts of hexamethylene diisocyanate, 8.8 parts of toluene diisocyanate, and 0.05 parts of dibutyltin dilaurate are added. The reaction is maintained at this temperature for 4 hours; S3: After the reaction is completed, the mixture is naturally cooled to 60°C and discharged. The product is washed three times with ethanol to obtain the final product.
[0082] The polycarbonate diol was purchased from Hubei Yamaide Biomedical Co., Ltd. as PCDL-2000.
[0083] 1,2-Propylene glycol was purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd. as an industrial-grade product.
[0084] The plasticizer is a combination of trioctyl citrate and epoxidized soybean oil in a mass ratio of 2.6:4.2.
[0085] The epoxidized soybean oil was purchased from Shandong Hongyunchang Chemical Technology Co., Ltd. as a premium plasticized grade epoxidized soybean oil product.
[0086] The chain extender is a composition of 1,2-propanediamine and diethyltoluenediamine in a mass ratio of 3.4:1.3.
[0087] The catalyst is dibutyltin dioctanoate.
[0088] The antioxidant is antioxidant 1076.
[0089] The preparation method of functional particles includes the following steps, by mass: S1: 2.8 parts carbon black and 0.68 parts titanium dioxide are mixed and added to 80 parts deionized water, 1.42 parts succinic anhydride and 0.26 parts isopropyl triisostearoyl titanate are added, and the mixture is heated to 65°C and kept at that temperature for 3 hours. After centrifugation and washing, premixed particles are obtained; S2: 4.4 parts premixed particles and 2.4 parts zinc nitrate are added to 80 parts DMF solvent, and the mixture is heated to 50°C and kept at that temperature for 3 hours. Then, 1.75 parts of 2,5-dihydroxyterephthalic acid DMF solution (20 parts in total) are added, the reaction vessel is sealed, and the temperature is raised to 128°C and 125°C. The reaction was stirred at rpm for 23.5 h. After the reaction was completed, the mixture was naturally cooled to room temperature, centrifuged and filtered, and washed with methanol to obtain the preproduct particles. S3: 4.8 parts of the preproduct particles were added to 100 parts of deionized water and ammonia water to adjust the pH to 9.8. 0.62 parts of tetraethyl orthosilicate and 0.14 parts of ethanolamine were added. The mixture was heated to 64℃ and kept at that temperature for 2.5 h. After the reaction was completed, the mixture was centrifuged and filtered, washed three times with ethanol, and dried to obtain the final product.
[0090] The average particle size of titanium dioxide is 5 nm; the average particle size of carbon black is 26 nm, and the corresponding particle size products were purchased from Mitsubishi Chemical in Japan.
[0091] The second aspect of this embodiment provides a method for preparing the above-mentioned thermoplastic polyurethane hot melt adhesive, specifically including the following steps: S1: Polyol composition, functional polymer, plasticizer and chain extender are preferentially added to the reaction vessel, the temperature is raised to 60°C, and the mixture is stirred at 80 rpm for 3 hours until the moisture content of the mixture is ≤0.03wt%; S2: The remaining raw materials are added to the reaction vessel, the stirring speed is increased to 120 rpm and the temperature is raised to 105°C, and the reaction is maintained at this temperature for 3 hours; S3: After the reaction is completed, the product is taken out, vacuum degassing is performed for 1 hour and the product is transferred to a storage container under dry inert gas protection to obtain the final product.
[0092] Example 3
[0093] Example 3 provides a thermoplastic polyurethane hot melt adhesive, which, by weight, comprises: 60.8 parts of a polyol composition, 16 parts of a polyisocyanate, 12 parts of a functional polymer, 8 parts of a plasticizer, 1.8 parts of a chain extender, 0.6 parts of a catalyst, 1.5 parts of an antioxidant, and 11.2 parts of functional particles.
[0094] The polyol composition is a combination of polyether polyol, polyester polyol and polyurea polyol, with a mass ratio of 3.5:4.2:0.8.
[0095] The polyether polyol is a copolyether triol of propylene oxide and ethylene oxide, with a number average molecular weight of 4000 Da and a hydroxyl value of 26.5 mgKOH / g. It was purchased from Shandong Poly Chemical Co., Ltd. under the model number 10LD28ZJ.
[0096] The polyester polyol is polyadipate polyester diol with a number average molecular weight of 3000 Da, which was purchased from Shandong Suihua Biotechnology Co., Ltd. and is a product of the corresponding molecular weight of the HY series.
[0097] The polyurea polyol has a polyurea content of 21.2%, a number average molecular weight of 6000 Da, and a hydroxyl value of 28.5 mgKOH / g. The polyurea polyol was purchased from Covestro as a Multranol 9151 product.
[0098] The polyisocyanate is hexamethylene diisocyanate.
[0099] The preparation method of the functional polymer includes the following steps, in parts by weight: S1: 10.5 parts of trimer 1,2-propylene glycol and 5.5 parts of polycarbonate diol are mixed evenly in a high-speed mixer and then dehydrated under vacuum at 125°C for 3 hours to obtain a premix; S2: The premix is added to a reaction vessel, heated to 80°C, and then 19.8 parts of hexamethylene diisocyanate, 5.2 parts of toluene diisocyanate, and 0.05 parts of dibutyltin dilaurate are added. The mixture is kept at this temperature for 4 hours; S3: After the reaction is completed, the mixture is naturally cooled to 60°C and discharged. The product is washed three times with ethanol to obtain the final product.
[0100] Polycarbonate diol was purchased from Hubei Yamade Biopharmaceutical Co., Ltd. under the model PCDL-2000.
[0101] The industrial grade trimer 1,2-propylene glycol was purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.
[0102] The plasticizer is a combination of trioctyl citrate and epoxidized soybean oil in a mass ratio of 4:5.5.
[0103] The epoxidized soybean oil was purchased from Shandong Hongyunchang Chemical Technology Co., Ltd. as a premium plasticized grade epoxidized soybean oil product.
[0104] The chain extender is a combination of 1,2-propanediamine and diethyltoluenediamine in a mass ratio of 4:1.
[0105] The catalyst is dibutyltin dioctoate.
[0106] The antioxidant is antioxidant 1076.
[0107] The preparation method of functional particles includes the following steps, by mass: S1: 2.5 parts carbon black and 0.8 parts titanium dioxide are mixed and added to 100 parts deionized water, 1.22 parts succinic anhydride and 0.38 parts isopropyl triisostearoyl titanate are added, and the mixture is heated to 65°C and kept at that temperature for 3 hours. After centrifugation and washing, premixed particles are obtained; S2: 5 parts premixed particles and 2.2 parts zinc nitrate are added to 100 parts DMF solvent, and the mixture is heated to 50°C and kept at that temperature for 3 hours. Then, 1.45 parts of 2,5-dihydroxyterephthalic acid DMF solution (20 parts in total) are added, the reaction vessel is sealed, and the temperature is raised to 128°C and 125°C. The reaction was stirred at rpm for 23.5 h. After the reaction was completed, it was naturally cooled to room temperature, centrifuged and filtered, and washed with methanol to obtain the preproduct particles. S3: 4.5 parts of the preproduct particles were added to 100 parts of deionized water and ammonia water to adjust the pH to 9.8. 0.8 parts of tetraethyl orthosilicate and 0.1 parts of ethanolamine were added. The temperature was raised to 64℃ and kept at 2.5 h. After the reaction was completed, it was centrifuged and filtered, washed with ethanol three times and dried to obtain the final product.
[0108] The average particle size of titanium dioxide is 5 nm; the average particle size of carbon black is 26 nm, and the corresponding particle size products were purchased from Mitsubishi Chemical in Japan.
[0109] The second aspect of this embodiment provides a method for preparing the above-mentioned thermoplastic polyurethane hot melt adhesive, specifically including the following steps: S1: Polyol composition, functional polymer, plasticizer and chain extender are preferentially added to the reaction vessel, the temperature is raised to 60°C, and the mixture is stirred at 80 rpm for 3 hours until the moisture content of the mixture is ≤0.03wt%; S2: The remaining raw materials are added to the reaction vessel, the stirring speed is increased to 120 rpm and the temperature is raised to 105°C, and the reaction is maintained at this temperature for 3 hours; S3: After the reaction is completed, the product is taken out, vacuum degassing is performed for 1 hour and the product is transferred to a storage container under dry inert gas protection to obtain the final product.
[0110] Example 4
[0111] Example 4 provides a thermoplastic polyurethane hot melt adhesive, which, by weight, comprises: 75 parts of a polyol composition, 22 parts of a polyisocyanate, 10 parts of a functional polymer, 5 parts of a plasticizer, 1.8 parts of a chain extender, 0.6 parts of a catalyst, 1.5 parts of an antioxidant, and 14 parts of functional particles.
[0112] The polyol composition is a combination of polyether polyol, polyester polyol and polyurea polyol, with a mass ratio of 2.5:3.5:1.2.
[0113] The polyether polyol is a co-ether triol of propylene oxide and ethylene oxide, with a number-average molecular weight of 4000 Da and a hydroxyl value of 26.5 mg KOH / g. It was purchased from Shandong Polychemical Co., Ltd. as product model 10LD28ZJ.
[0114] The polyester polyol is polyadipate polyester diol with a number average molecular weight of 3000 Da, which was purchased from Shandong Suihua Biotechnology Co., Ltd. and is a product of the corresponding molecular weight of the HY series.
[0115] The polyurea polyol has a polyurea content of 21.2%, a number average molecular weight of 6000 Da, and a hydroxyl value of 28.5 mgKOH / g. The polyurea polyol was purchased from Covestro as a Multranol 9151 product.
[0116] The polyisocyanate is hexamethylene diisocyanate.
[0117] The preparation method of the functional polymer includes the following steps, in parts by weight: S1: 20 parts of trimer 1,2-propylene glycol and 10 parts of polycarbonate diol are mixed evenly in a high-speed mixer and then dehydrated under vacuum at 125°C for 3 hours to obtain a premix; S2: The premix is added to a reaction vessel, heated to 80°C, and then 15.2 parts of hexamethylene diisocyanate, 9.8 parts of toluene diisocyanate, and 0.05 parts of dibutyltin dilaurate are added. The reaction is maintained at this temperature for 4 hours; S3: After the reaction is completed, the mixture is naturally cooled to 60°C and discharged. The product is washed three times with ethanol to obtain the final product.
[0118] Polycarbonate diol was purchased from Hubei Yamade Biopharmaceutical Co., Ltd. under the model PCDL-2000.
[0119] The industrial grade trimer 1,2-propylene glycol was purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.
[0120] The plasticizer is a composition of trioctyl citrate and epoxidized soybean oil, and the mass ratio of the two is 2:4.2.
[0121] The epoxidized soybean oil was purchased from Shandong Hongyunchang Chemical Technology Co., Ltd. as a premium plasticized grade epoxidized soybean oil product.
[0122] The chain extender is a composition of 1,2-propylene diamine and diethyltoluenediamine, and the mass ratio of the two is 3:1.4.
[0123] The catalyst is dibutyltin dioctoate.
[0124] The antioxidant is antioxidant 1076.
[0125] The preparation method of functional particles comprises the following steps, calculated by mass: S1: 3 parts of carbon black and 0.5 parts of titanium dioxide are mixed and added to 100 parts of deionized water, 1.48 parts of succinic anhydride and 0.2 parts of triisostearyl titanate isopropyl are added, the temperature is raised to 65°C and kept for reaction for 3 hours, and premixed particles are obtained by centrifugation and washing; S2: 4 parts of premixed particles and 2.5 parts of zinc nitrate are added to 100 parts of DMF solvent, the temperature is raised to 50°C and kept for reaction for 3 hours, and then 1.8 parts of 2,5-dihydroxyterephthalic acid DMF solution (a total of 20 parts) are added, the reactor is sealed, and the temperature is raised to 128°C, 125 The reaction was stirred at rpm for 23.5 h. After the reaction was completed, the mixture was naturally cooled to room temperature, centrifuged and filtered, and washed with methanol to obtain the preproduct particles. S3: 5 parts of the preproduct particles were added to 100 parts of deionized water and ammonia water to adjust the pH to 9.8. 0.5 parts of tetraethyl orthosilicate and 0.15 parts of ethanolamine were added, and the mixture was heated to 64℃ and kept at that temperature for 2.5 h. After the reaction was completed, the mixture was centrifuged and filtered, washed three times with ethanol, and dried to obtain the final product.
[0126] The average particle size of titanium dioxide is 5 nm; the average particle size of carbon black is 26 nm, and the corresponding particle size products were purchased from Mitsubishi Chemical in Japan.
[0127] The second aspect of this embodiment provides a method for preparing the above-mentioned thermoplastic polyurethane hot melt adhesive, specifically including the following steps: S1: Polyol composition, functional polymer, plasticizer and chain extender are preferentially added to the reaction vessel, the temperature is raised to 60°C, and the mixture is stirred at 80 rpm for 3 hours until the moisture content of the mixture is ≤0.03wt%; S2: The remaining raw materials are added to the reaction vessel, the stirring speed is increased to 120 rpm and the temperature is raised to 105°C, and the reaction is maintained at this temperature for 3 hours; S3: After the reaction is completed, the product is taken out, vacuum degassing is performed for 1 hour and the product is transferred to a storage container under dry inert gas protection to obtain the final product.
[0128] Comparative Example 1
[0129] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the thermoplastic polyurethane hot melt adhesive, by mass, consists of: 80.5 parts of polyol composition, 23.4 parts of polyisocyanate, 4.5 parts of functional polymer, 6.5 parts of plasticizer, 1.8 parts of chain extender, 0.6 parts of catalyst, 1.5 parts of antioxidant, and 10.2 parts of functional particles.
[0130] Comparative Example 2
[0131] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the thermoplastic polyurethane hot melt adhesive, by mass, consists of: 71.5 parts of polyol composition, 20 parts of polyisocyanate, 13.5 parts of functional polymer, 6.5 parts of plasticizer, 1.8 parts of chain extender, 0.6 parts of catalyst, 1.5 parts of antioxidant, and 5.5 parts of functional particles.
[0132] Comparative Example 3
[0133] The specific implementation method of this comparative example is basically the same as that of Example 1, except that the polyol composition is a composition of polyether polyol, polyester polyol and polyurea polyol, and the mass ratio of the three is 3:5:0.4.
[0134] Comparative Example 4
[0135] The specific implementation method of this comparative example is basically the same as that of Example 1, except that the polyester polyol is poly(adipic acid polyester diol) with a number average molecular weight of 1000 Da, which is a product of the corresponding molecular weight of the HY series purchased from Shandong Suihua Biotechnology Co., Ltd.
[0136] Comparative Example 5
[0137] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the functional polymer comprises the following steps, calculated in parts by mass: S1: 5.5 parts of trimer 1,2-propylene glycol and 14.5 parts of polycarbonate diol are mixed uniformly in a high-speed mixer, and then vacuum-dehydrated at 125° C. for 3 hours to obtain a premix; S2: the premix is added to a reaction vessel, and after heating to 80° C., 6.5 parts of hexamethylene diisocyanate, 12.5 parts of toluene diisocyanate and 0.05 parts of dibutyltin dilaurate are added, and the mixture is kept warm for reaction for 4 hours; S3: after the reaction is completed, the mixture is naturally cooled to 60° C. and discharged, and the product is washed with ethanol three times to obtain the product.
[0138] Comparative Example 6
[0139] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the functional polymer comprises the following steps, calculated in parts by mass: S1: dehydrating 18.5 parts of trimer 1,2-propylene glycol in a vacuum at 125°C for 3 hours; S2: adding trimer 1,2-propylene glycol to a reaction vessel, heating to 80°C, adding 32 parts of diphenylmethane diisocyanate, 2.5 parts of toluene diisocyanate and 0.05 parts of dibutyltin dilaurate, and keeping the temperature for reaction for 4 hours; S3: after the reaction is completed, naturally cooling to 60°C and discharging, and the product is obtained after being washed three times with ethanol.
[0140] Comparative Example 7
[0141] The specific implementation method of this comparative example is basically the same as that of Example 1, except that the preparation method of the functional particles includes the following steps, in parts by mass: S1: 4.5 parts of carbon black and 0.35 parts of titanium dioxide are mixed and added to 120 parts of deionized water, 0.85 parts of succinic anhydride and 0.12 parts of triisostearoyl titanate isopropyl ester are added and the mixture is heated to 65°C and kept at that temperature for 3 hours. After centrifugation and washing, premixed particles are obtained; S2: 6.5 parts of premixed particles and 2.4 parts of zinc nitrate are added to 80 parts of DMF solvent, the mixture is heated to 50°C and kept at that temperature for 3 hours. Then, 1.75 parts of 2,5-dihydroxyterephthalic acid DMF solution (20 parts in total) are added, the reaction vessel is sealed, and the temperature is raised to 128°C and 125°C. The reaction was stirred at rpm for 23.5 h. After the reaction was completed, the mixture was naturally cooled to room temperature, centrifuged and filtered, and washed with methanol to obtain the preproduct particles. S3: 4.8 parts of the preproduct particles were added to 100 parts of deionized water and ammonia water to adjust the pH to 9.8. 0.62 parts of tetraethyl orthosilicate and 0.14 parts of ethanolamine were added. The mixture was heated to 64℃ and kept at that temperature for 2.5 h. After the reaction was completed, the mixture was centrifuged and filtered, washed three times with ethanol, and dried to obtain the final product.
[0142] Comparative Example 8
[0143] The specific implementation method of this comparative example is basically the same as that of Example 1, except that the preparation method of the functional particles includes the following steps, in parts by mass: S1: 2.8 parts of carbon black and 0.68 parts of titanium dioxide are mixed and added to 80 parts of deionized water, 1.42 parts of succinic anhydride and 0.26 parts of triisostearoyl titanate isopropyl ester are added and the mixture is heated to 65°C and kept at that temperature for 3 hours. After centrifugation and washing, premixed particles are obtained; S2: 4.4 parts of premixed particles and 4.5 parts of zinc nitrate are added to 150 parts of DMF solvent, the mixture is heated to 50°C and kept at that temperature for 3 hours, then 2.9 parts of 2,5-dihydroxyterephthalic acid DMF solution (30 parts in total) are added, the reaction vessel is sealed, and the temperature is raised to 128°C and 125°C. The reaction was stirred at rpm for 23.5 h. After the reaction was completed, the mixture was naturally cooled to room temperature, centrifuged and filtered, and washed with methanol to obtain the preproduct particles. S3: 5.8 parts of the preproduct particles were added to 100 parts of deionized water and ammonia water to adjust the pH to 9.8. 0.32 parts of tetraethyl orthosilicate and 0.05 parts of ethanolamine were added, and the mixture was heated to 64℃ and kept at that temperature for 2.5 h. After the reaction was completed, the mixture was centrifuged and filtered, washed three times with ethanol, and dried to obtain the final product.
[0144] Comparative Example 9
[0145] The specific implementation method of this comparative example is basically the same as that of Example 1, except that the average particle size of titanium dioxide is 45nm and the average particle size of carbon black is 42nm, which are purchased from Mitsubishi Chemicals of Japan.
[0146] Performance evaluation
[0147] Mechanical properties: The elongation at break of the polyurethane hot melt adhesives prepared in the examples and comparative examples was tested using a universal testing machine at 25℃ and 50% relative humidity. The average value of 10 tests was recorded in Table 1.
[0148] Adhesion: In accordance with standard GB / T 2791-1995, the polyurethane hot melt adhesives of the examples and comparative examples were subjected to T-peel strength adhesion tests. The initial tack and final tack were measured, and the test values were taken as the average of 10 tests and recorded in Table 1.
[0149] Waterproofing: The surface waterproofing performance of the polyurethane hot melt adhesives prepared in the examples and comparative examples was tested using the droplet method. The test droplet size was 2.5 μL, the test time was 15 s, and the surface water contact angle was obtained. The test value was the average of 10 tests and recorded in Table 1.
[0150] Aging resistance: After curing the polyurethane hot melt adhesive prepared in the examples and comparative examples, samples of 2cm×2cm×0.2cm were prepared and placed in a constant temperature and humidity chamber at 68±2℃ and 75±3% relative humidity for 6 months. After 6 months, the samples were recorded for yellowing, oxidation, cracking, blistering and hydrolysis damage. If any of these occurred, the samples were considered unqualified, otherwise they were considered qualified. 50 samples were tested in each group, and the pass rate of the samples was recorded in Table 1.
[0151] Table 1 Performance Test Results
[0152]
[0153] From the embodiments and comparative examples of this application, as well as the data results in Table 1, it can be seen that embodiments 1-4 of this application have significant advantages over comparative examples 1-9 in terms of mechanical properties, waterproof properties, antistatic properties, and aging resistance. This is mainly due to the combined effect of the functional polymers, functional particles, and other coordinating technologies specified in this application. Comparative examples 1-9, on the other hand, did not adopt the technical solutions specified in this application, resulting in significant disadvantages in the above performance tests. This further proves the necessity of the technical solutions specified in this application for the technical effects of this application and for solving technical problems.
Claims
1. A thermoplastic polyurethane hot melt adhesive, characterized in that: The raw materials are, by mass: 50-80 parts of polyol composition, 15-25 parts of polyisocyanate, 8-12 parts of functional polymer, 5-8 parts of plasticizer, 1-2 parts of chain extender, 0.3-1.2 parts of catalyst, 1-3 parts of antioxidant, and 10-15 parts of functional particles; The polyisocyanate is hexamethylene diisocyanate; The preparation method of the functional polymer comprises the following steps: S1: after trimer 1,2-propylene glycol and polycarbonate diol are uniformly mixed in a high-speed mixer, vacuum dehydration is carried out at 120-130° C. for 2-3 hours to obtain a premix; S2: adding the premix into a reaction container, heating it to 70-85° C., adding hexamethylene diisocyanate, toluene diisocyanate and dibutyltin dilaurate, and keeping the temperature for reaction for 2-4 hours; S3: after the reaction is completed, naturally cooling to 60-65° C., discharging the material, and after the product is washed 2-3 times with ethanol, cutting and granulating the product to obtain the functional polymer; The mass ratio of trimer 1,2-propylene glycol, polycarbonate diol, hexamethylene diisocyanate and toluene diisocyanate is (10-20): (5-10): (15-20): (5-10); The preparation method of the functional particles comprises the following steps: S1: mixing carbon black and titanium dioxide and adding them into deionized water, adding succinic anhydride and isopropyl triisostearoyl titanate, heating to 60-70°C for reaction for 2-3 hours, and centrifugation washing to obtain premixed particles; S2: adding the premixed particles and zinc nitrate into DMF solvent, heating to 45-55°C for reaction for 3-4 hours, then adding DMF solution of 2,5-dihydroxyterephthalic acid, sealing the reactor, heating to 125-130°C, stirring at 120-150rpm for reaction for 22-26 hours, cooling naturally to room temperature after the reaction is completed, centrifugation filtering, and washing with methanol to obtain preproduct particles; S3: adding the preproduct particles into deionized water and ammonia water to adjust the pH to 9.5-10, adding tetraethyl orthosilicate and ethanolamine, heating to 60-65°C for reaction for 2-3 hours, centrifugation filtering after completion, ethanol cycle washing 2-3 times and drying to obtain; The mass ratio of carbon black, titanium dioxide, succinic anhydride and isopropyl triisostearyl titanate is (2.5-3): (0.5-0.8): (1.2-1.5): (0.2-0.4); The mass ratio of the premixed particles, zinc nitrate and 2,5-dihydroxyterephthalic acid is (4-5): (2.2-2.5): (1.4-1.8); The polyol composition is a composition of polyether polyol, polyester polyol and polyurea polyol; The number average molecular weight of the polyester polyol is 2000-3000Da; The polyester polyol is polyadipate polyester diol; the mass ratio of the polyether polyol, polyester polyol and polyurea polyol is (2.5-3.5): (3.5-4.2): (0.8-1.2); the functionality of the polyether polyol is 3; the number average molecular weight of the polyether polyol is 3000-4000Da; the polyurea content of the polyurea polyol is 15-23%; The average particle size of the titanium dioxide is 5 to 10 nm; The average particle size of the carbon black is 20-30 nm.
2. The thermoplastic polyurethane hot melt adhesive according to claim 1, characterized in that: The mass ratio of the polyol composition, the polyisocyanate and the functional polymer is (6-7.5): (1.6-2.2): (1-1.2); the mass ratio of the polyol composition, the plasticizer and the functional particles is (6-7.5): (0.5-0.8): (1.1-1.4); and the polyether polyol is a copolyether triol of propylene oxide and ethylene oxide.
3. The thermoplastic polyurethane hot melt adhesive according to claim 2, characterized in that: The number average molecular weight of the polyurea polyol is 5000-6500 Da; the hydroxyl value of the polyether polyol is 25-30 mgKOH / g.
4. The thermoplastic polyurethane hot melt adhesive according to claim 3, characterized in that: The hydroxyl value of the polyurea polyol is 25-33 mgKOH / g.
5. The thermoplastic polyurethane hot melt adhesive according to claim 4, characterized in that: The catalyst is dibutyltin dilaurate or dibutyltin dioctoate; the antioxidant is antioxidant 1076.
6. The thermoplastic polyurethane hot melt adhesive according to claim 5, characterized in that: The plasticizer is a composition of trioctyl citrate and epoxidized soybean oil; the mass ratio of trioctyl citrate to epoxidized soybean oil is (2-4): (4-5.5).
7. The thermoplastic polyurethane hot melt adhesive according to claim 6, characterized in that: The chain extender is a composition of 1,2-propylene diamine and diethyl toluenediamine; the mass ratio of the 1,2-propylene diamine to diethyl toluenediamine is (3-4): (1-1.5).
8. A method for preparing the thermoplastic polyurethane hot melt adhesive according to any one of claims 1 to 7, characterized in that: The specific steps include: S1: Add the polyol composition, functional polymer, plasticizer and chain extender to the reaction container, raise the temperature to 55-60°C, and stir at 60-80rpm for 2-4h until the moisture content of the mixture is ≤0.03wt%; S2: Add the remaining raw materials to the reaction container, increase the speed to 100-140rpm and raise the temperature to 90-110°C, and keep the temperature for reaction for 2-4h; S3: After the reaction is completed, take out the product, vacuum degas for 1-1.5h and transfer it to a storage container for drying under inert gas protection.
9. Application of the thermoplastic polyurethane hot melt adhesive according to any one of claims 1 to 7 in the automotive industry, electronic products, packaging, and construction fields.
